Genomic Instability and Cancer Metastasis Mechanisms, Emerging Themes, and Novel Therapeutic Strategies - Maxwell, Chris; Roskelley, Cal (Cancer Metastasis - Biology and Treatment,, 2015)
Metastasis is the primary cause of mortality associated with cancer, and tumor genomic heterogeneity is a likely source for the cells that support cancer progression, resistance to therapy, and disease relapse. This book connects cancer metastasis with genomic instability in a comprehensive manner. Section 1  outlines the fundamental mechanisms responsible for these cellular and tissue phenotypes. Section 2 discusses in silico, in vitro, and in vivo models used for the experimental study of these processes. Section 3 reviews emerging themes (ex., microenvironment, mechanotransduction, and immunomodulation), and Section 4 highlights new therapeutic approaches to overcome the unique challenges presented by the heterogeneous and metastatic tumor. This book is intended for undergraduates and postgraduates with an interest in the areas of medicine, oncology, and cancer biology as well as for the content expert searching for thorough reviews of current knowledge in these areas.